Rare earth phosphors based on spherical infinite coordination polymers - Arroyos, Guilherme [UNESP]; Frem, Regina Célia Galvão [UNESP] (Royal Society of Chemistry (RSC), 2018)
A novel luminescent infinite coordination polymer (Tb-M), constructed by the interaction between Tb 3+ ions and 3,5-pyrazoledicarboxylate and malonate linkers, was prepared by water microwave-assisted synthesis. The material self-assembles into amorphous microspherical particles. Under UV excitation, a very intense green luminescence is observed by the naked eye at room temperature for Tb-M. A Gd 3+ analogue compound (Gd-M) was also synthesized. Successful attempts at codoping Tb-M and Gd-M samples with Eu 3+ and Dy 3+ ions were carried out and different emission colors were obtained, including white-light emission.